(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Achieving food security and independence involves overcoming various risks and threats. The most probable and dangerous risks should be recognized: natural, weather and man-made; economic and industrial; innovative. Macroeconomic risks, including those related to the global market situation, as well as political risks of a national and global scale, have a strong impact on the agri-food complex. Threats to achieving food security are associated with a low-income level of a significant part of the population, underdeveloped infrastructure, depreciation of fixed production assets, a shortage of personnel in agriculture, and an inefficient management system. The most important aspects of food security are considered, the main criteria and measures for the formation of effective mechanisms for ensuring food security.